Vulnerability at the Intersection of Climate and Identity: Local Resilience Practices and Climate Change Adaptation among Uzbek Turks in Northern Afghanistan (Third Sector Social Economic Review, 2025)
Climate change is not merely a process of environmental degradation in states with limited institutional capacity, weak governance structures, and chronic socio-political instability, it constitutes a structural risk that undermines societal resilience mechanisms and deepens multidimensional vulnerabilities. In rural areas dominated by agriculture-based livelihoods, climate shocks directly affect subsistence resources, thereby increasing social, economic, and spatial vulnerability. This study focuses on the Uzbek Turks living in the northern provinces of Afghanistan and examines the concept of environmental vulnerability in the context of intersecting structural inequalities such as ethnic identity, rural marginalization, and gender. The research aims to make visible the resilience mechanisms developed by a micro-ethnic community under climate stress and the local knowledge systems that shape these processes. Due to restricted field access, the dataset consists of field reports prepared by international organizations, analyzed through secondary document analysis. The theoretical framework is grounded in W. Neil Adger’s climate justice perspective and social vulnerability theory. The findings reveal that the vulnerabilities faced by the Uzbek Turks are not limited to climate exposure but are compounded by intersecting structural disadvantages, including limited access to public services, inadequate water infrastructure, exclusion from ethnic representation, gender inequalities, and early marriage. Within this context, hashar (collective labor), karez (traditional underground water management), and observational knowledge of rainfall patterns are embedded in the community’s cultural memory as resilience practices however, the sustainability of such systems is currently under serious threat. The study argues that climate policies targeting vulnerable communities should not be confined to technical interventions, but rather be restructured within a multi-layered justice perspective that recognizes local knowledge systems, incorporates gender equality, and develops targeted adaptation strategies for micro-ethnic communities.
Keywords: Climate justice, Climate vulnerability; Intersectionality; Local knowledge systems; Uzbek Turks – Afghanistan.